2005
DOI: 10.1080/00207450590519175
|View full text |Cite
|
Sign up to set email alerts
|

Lavender Fragrance Cleansing Gel Effects on Relaxation

Abstract: Alertness, mood, and math computations were assessed in 11 healthy adults who sniffed a cosmetic cleansing gel with lavender floral blend aroma, developed to be relaxing using Mood Mapping. EEG patterns and heart rate were also recorded before, during, and after the aroma session. The lavender fragrance blend had a significant transient effect of improving mood, making people feel more relaxed, and performing the math computation faster. The self-report and physiological data are consistent with relaxation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 33 publications
4
66
0
1
Order By: Relevance
“…To our knowledge, few studies have shown such discrepant effects of lavender inhalation on the mind and body. Nevertheless, Field et al [2] reported improved performance in a calculation task under lavender aroma inhalation, while Heuberger et al [20] reported improved performance in a cognitive task (vigilance task) under inhalation of lialyl-acetate, a major compound of lavender essential oil. Our ndings seem to be consistent with the ndings of these behavioral studies.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, few studies have shown such discrepant effects of lavender inhalation on the mind and body. Nevertheless, Field et al [2] reported improved performance in a calculation task under lavender aroma inhalation, while Heuberger et al [20] reported improved performance in a cognitive task (vigilance task) under inhalation of lialyl-acetate, a major compound of lavender essential oil. Our ndings seem to be consistent with the ndings of these behavioral studies.…”
Section: Figmentioning
confidence: 99%
“…Lavender, the most commonly used aroma in aromatherapy, functions as an effective medicament for neurological disorders [1], improves task performance [2], decreases blood pressure [3] and improves sleep quality [4]. On the other hand, jasmine, which is considered a stimulating aroma, induces autonomic arousal, such as enhancement of systolic and diastolic blood pressure [5].…”
Section: Introductionmentioning
confidence: 99%
“…For one, it has been shown that exposure to lavender increases cortical beta power, accompanied by drowsiness (Diego et al, 1998;Field et al, 2005;Lorig, Herman, Schwartz, & Cain, 1990). For another, Gross et al (2004) found that increased long-range phase synchronization in the beta band was associated with a less pronounced AB.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, sedative effect of lavender smell on rats was determined (Buchbauer, Jirovetz, Jager, Dietrich and Plank, 1991). There is also a great deal of evidence that aromatherapy affects mood and behavior in a positive way (Diego et al, 1998;Field et al, 2005;Herz, 2009;Rho, Han, Kim and Lee, 2006).…”
Section: Aromatherapymentioning
confidence: 99%